A typology of climatopias: visualizations, motivations, and transformations - Alizé Carrère; Kenneth Broad; Joanna Lombard; Denis Hector; Katharine J Mach (Environmental Research: Climate)
Climate change is catalyzing responses for innovation in the built environment. Architecture and design firms are at the forefront of these endeavors, applying cutting-edge technologies to shape and visualize potential futures in ways they claim to be revolutionary or transformational. Despite the proliferation of such proposals, little analysis of this work has emerged. This paper seeks to assess this field of ‘climatopias,’ that is, projects that propose a form of utopian thinking or planning for climate-responsive design, and evaluate their transformational potential for the built environment. For 66 such architectural and urban planning projects, we analyze their types and attributes, with a focus on dominant motivations and the extent of sociopolitical transformation. Six key types of climatopias emerge: projects that (1) Fortify, (2) Forest, (3) Float, (4) Reduce, (5) Re-use, or (6) Retreat in pursuit of climate solutions for the built environment. 41% of the projects evaluated do not have any sociopolitical transformation present in their designs, meaning they do not rigorously qualify as climatopias despite their visual appearances and could risk reinforcing sociopolitical inequities and harms. Of projects rigorously fulfilling climatopia criteria for sociopolitical transformation, only 4 projects (10%) are all-encompassing in their proposed transformation, especially through engaging with political aspects of the design, such as ownership and governance. The Forest type demonstrates the least sociopolitical transformation across design proposals and projects, while the Reduce and Re-use types demonstrate the most. Despite growing calls for climate-resilient solutions combining mitigation and adaptation goals, decarbonization and climate risk reduction motivations rarely appear together in climate-responsive designs and projects. As designers advance this work, the typology presented here can serve as a reference guide to assist in expanding considerations of the range of transformational change and co-benefits required to address and adapt to climate change.